2000
DOI: 10.2135/cropsci2000.4051277x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Seed Protein Concentration in Soybean by Supra‐Optimal Nitrogen Supply

Abstract: nificant barriers to development of high-protein commercial cultivars. The physiological and biochemical basis for increased seed proteinSoybean SPC is inherited as a quantitative trait (Burconcentrations (SPC) observed in restriction-index, recurrent-selec- ton, 1987) and influenced by environmental effects tion breeding programs with soybean [Glycine max (L.) Merr.] are poorly understood. The hypothesis that soybean SPC is regulated by (Burton, 1988). Generally the trait is much less influthe supply of nitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
39
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 28 publications
4
39
0
Order By: Relevance
“…Variability in protein and oil content existed among the nodes (Escalante and Wilcox 1993a;Bennett et al 2003;Guleria et al 2007) and these differences have been attributed to environmental factors (Wolf et al 1982;Maestri et al 1998). Nakasathein et al (2000) demonstrated that the relative mobility of each nutrient at different node position generated high nitrogen to sulphur ratio in the apical position of the stem axis, which was conducive to accumulate enhanced dry matter rich in the protein subunits (Bennett et al 2003). Correspondingly nitrogen and sulfur would be less in basal part of the plant making available the precursors for the synthesis of lipids.…”
Section: Resultsmentioning
confidence: 99%
“…Variability in protein and oil content existed among the nodes (Escalante and Wilcox 1993a;Bennett et al 2003;Guleria et al 2007) and these differences have been attributed to environmental factors (Wolf et al 1982;Maestri et al 1998). Nakasathein et al (2000) demonstrated that the relative mobility of each nutrient at different node position generated high nitrogen to sulphur ratio in the apical position of the stem axis, which was conducive to accumulate enhanced dry matter rich in the protein subunits (Bennett et al 2003). Correspondingly nitrogen and sulfur would be less in basal part of the plant making available the precursors for the synthesis of lipids.…”
Section: Resultsmentioning
confidence: 99%
“…Taking into consideration the gain obtained in protein rates as a result of the cultivation in vitro with 20 and 40 mM glutamine concentrations, it was evident that the increase in protein rate occurred when the glutamine was increased. Nakasathien et al (2000) suggested that a cultivar with a regular concentration of protein in the seed had a biochemical capability of synthesizing more protein when N was available. When the cultivars were compared, there was an important statistical difference (P<0.05) for all the glutamine concentrations in both the cultivations in vitro and in vivo, while the CD 206 cultivar presented the highest averages of protein rates.…”
Section: Resultsmentioning
confidence: 99%
“…GDH is an enzyme of N metabolism that usually reaches a higher degree of activity during senescence (Ragster & Chrispeels, 1981;Laurière & Daussand, 1983). NH 4 + is available for transformation in the composts of N transport, such as glutamine and asparagine (Ghosh et al, 1995;Nakasathien et al, 2000), and some of the ions are converted into NH 3 according to the following balanced reaction:…”
Section: Nitrogen Lossesmentioning
confidence: 99%